Assessing the Role of the United Nations in Countering Global Terrorism: Issues and Challenges - Barshep, Timbyen (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
Global attention has shifted to terrorism since 9/11 multiple terror attacks on the United States. The study examines the efficacy of the United Nations in galvanizing global effort against terrorism, 2001-2021. It argues that while the global body didn’t envision the emergence of terrorism, the global body has strained apace with global issues, more so with terrorism both before and especially since the multiple terror attacks on the United States on 9/11. The United Nations has provided an outlet on global response. Employing the use of secondary source and relying on archival materials, the study found that the UN has since stopped efforts in leading consensus on the devastating impact of terrorism on global security if not quickly checked. Thus, unlike arguments by some critics, the UN, especially since 2001 has remained unrelenting in arguing for a global consensus for a unanimity to define terrorism. The study recommends that terrorism can best be defeated with a shift in the structure of the international system from the perception of the ’’we versus them’’ approach to an all-embracing system coordinated by the United Nations.